GAMBARAN TERJADINYA PERNIKAHAN DINI AKIBAT PERGAULAN BEBAS - Puji Hastuti; Fajaria Nur Aini (Jurnal Riset Kesehatan, 2016)
The trend of early marriage in Banyumas increasing in every year. It caused by low levels of education and social conditions of the local culture. The couples who had early marriage usually caused by the women had been pregnant before they married. Risks such as domestic violence, don’t have financial preparation yet, cause adverse effects for women and blamed for the high divorce from public. The type of research is field research with data collection through the documentation, in-depth interview, an observation with the subjects of early marriage. Characteristic of the research is qualitative and descriptive, sites in the district of Baturraden, Banyumas. Respondents who forced to marry because they pregnant, altough they are still young and they do not understand what the impact. Pregnancy results from sexual intercourse before marriage with her boyfriend, because the request girlfriend and stimulation of the viewing of pornography, which is done at home when sleepy.